HUBUNGAN PERILAKU INTERPERSONAL GURU DAN PARTISIPASI PESERTA DIDIK DENGAN HASIL BELAJAR BIOLOGI DI SMA - Yusnia Eka Putri; Supriyatin Supriyatin; Eka Putri Azrai (Florea : Jurnal Biologi dan Pembelajarannya, 2020)
Teacher’s interpersonal behavior, play a critical role on teacher-student interaction. Teacher-student interaction related to student’s participation on learining process. Student’s participation related to student’s outcome. The aim of this research is to investigate whether there is a correlation between teacher’s interpersonal behavior ans student’s participation with student outcome. The research was conducted at SMAN 2 Bekasi on October-November 2018. The total sample was 114 students of Mathematics and Science Programe at eleventh grade. The method used for this research is descriptive method. The result showed that there is a positive correlation between teacher’s interpersonal behavior and student’s biology outcome, a positive correlation between student’s participation and student’s biology outcome, a positive correlation between teacher’s interpersonal behavior and student’s participation, and also a positive correlation between teacher’s interpersonal behavior and student’s participation with student’s biology outcome.Keywords: learning outcome, participation, teacher’s interpersonal behavior